2016
DOI: 10.3390/app6120390
|View full text |Cite
|
Sign up to set email alerts
|

Wing Geometry and Kinematic Parameters Optimization of Flapping Wing Hovering Flight

Abstract: How to efficiently mimic the wing shape and kinematics pattern of an able hovering living flier is always a concern of researchers from the flapping wing micro aerial vehicles community. In this work, the separate or combined optimizations of wing geometry or/and wing kinematic parameters are systematically performed to minimize the energy of hovering flight, firstly on the basis of analytically extended quasi-steady aerodynamic model by using hybrid genetic algorithm. Before the elaboration of the optimizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…The analytical model accounting for only the translational mechanism was also adopted by Nabawy and Crowther [8] to acquire the minimum power constrained by a given lift, and they concluded that the flapping angle with a triangular profile and the pitching angle with a rectangular profile consume the lowest power with the given wing geometry parameters. X. Ke and W. Zhang [30] adopted a revised quasi-steady aerodynamic model to evaluate the wing performance of dynamically scaled fruit flies. Optimizations of wing geometry and kinematic parameters were conducted, revealing that the optimal flapping angle followed a harmonious profile, while the optimal pitching angle exhibited a rounded trapezoidal profile with a faster time scale of pitching reversal.…”
Section: Introductionmentioning
confidence: 99%
“…The analytical model accounting for only the translational mechanism was also adopted by Nabawy and Crowther [8] to acquire the minimum power constrained by a given lift, and they concluded that the flapping angle with a triangular profile and the pitching angle with a rectangular profile consume the lowest power with the given wing geometry parameters. X. Ke and W. Zhang [30] adopted a revised quasi-steady aerodynamic model to evaluate the wing performance of dynamically scaled fruit flies. Optimizations of wing geometry and kinematic parameters were conducted, revealing that the optimal flapping angle followed a harmonious profile, while the optimal pitching angle exhibited a rounded trapezoidal profile with a faster time scale of pitching reversal.…”
Section: Introductionmentioning
confidence: 99%
“…Two main strategies exist to study the aerodynamic characteristics: an experiment-based approach [17][18][19] or a model-based approach [20][21][22]. The disadvantage of the purely experimental approach is that a limited number of possible configurations can be considered and a model-supported approach may solve this issue.…”
Section: Introductionmentioning
confidence: 99%
“…A final design was reached fast and consistently by a genetic algorithm, including different sampling criteria and multiple surrogates in the gene evolution process, despite noisy data measurements and small manufacturing inaccuracies. The combined optimization of wing shape and kinematics by Ke and Zhang [26] led to solutions with lower flapping frequency, larger wing geometries and lower power density in comparison to the solutions from the individual optimization of shape and kinematics. Very recently, Lee and Lua [27] focused on the pitching motion of a hawk moth in hovering flight and used a two-stage optimization method to identity the influence of the pitch angle evolution to the flapping wing performance of complex, insect-like motion profiles.…”
Section: Introductionmentioning
confidence: 99%